COMHHPREHENSIVE MIDWIFERY CARE FOR MRS. N AT INDEPENDENT MIDWIFERY PRACTICE (BPM) HUTRI PRAWITA SUBULUSSALAM CITY - Suci Rahmawati; Ricca Nophia Amra; Fitriani Bancin; Rahayu Ningsih; Ratnawati Bancin (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Pregnancy, labor, postpartum, and newborn periods are continuous physiological processes, yet they still carry risks of life-threatening complications for both mother and baby. Based on data from the Subulussalam City Health Office in 2025, maternal death cases and 25 infant death cases were recorded. The Continuity of Care (CoC) approach is an effective strategy for early detection of high-risk factors and reducing Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR).Objective: To provide comprehensive and continuous midwifery care (Continuity of Care) to Mrs. N starting from the third trimester of pregnancy, labor, postpartum period, newborn, up to family planning (KB) services using a SOAP-based midwifery management documentation approach.Method: This study uses a descriptive qualitative method with a comprehensive case study approach. The subject of the study was Mrs. N, 26 years old, G3P2A0. Primary data collection was conducted through direct observation, interviews, and physical examination (head-to-toe and Leopold’s palpation). Secondary data were obtained from the Maternal and Child Health (KIA) handbook, ultrasound (USG) results, and the PMB register. Care was implemented at PMB Hutri Prawita Bancin, AM.Keb from March to July 2026.Results: Antenatal care (ANC) was provided across 2 visits at 30 weeks 2 days and 38 weeks of gestation, showing that the maternal and fetal conditions were within normal limits. On May 26, 2026, at 05:00 AM WIB, the mother entered the active phase of the first stage of labor (INC). The entire process from pregnancy to labor was well-documented.Conclusion: The implementation of comprehensive midwifery care for Mrs. N proceeded according to midwifery service standards, and no complications or pathological difficulties were found in either the mother or the fetus.